(untitled) (Interdisciplinary Studies Journal, 2025)
The article analyzes the theoretical and political foundations of inclusive education, focusing on social approaches to disability and their relationship with teaching practice. The aim is to discuss school inclusion based on the curriculum as an expression of the right to education, rejecting its adjectivization and instrumentalization. The methodology adopted was of a theoretical-analytical nature, based on a literature review. The study is based on references from critical pedagogy, the sociology of disability, epistemologies of the South and critical anthropology. The analyses reveal that inclusion, often mobilized as a normative discourse, operates as a device for governing subjects, reinforcing practices of medicalization and individual teacher accountability. It also highlights the importance of ethnography in understanding the meanings of inclusion in everyday school life. The discussions indicate that access to knowledge should be the axis of inclusion, shifting the focus from adaptation to guaranteeing the right to learn. The conclusion is that an effective inclusion policy requires valuing the common curriculum, strengthening the school’s public commitment and recognizing teaching practice as a political and collective act.